2020
DOI: 10.1007/s12020-020-02424-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lanreotide autogel 120 mg at extended dosing intervals for acromegaly

Abstract: Purpose Recent data indicate that extended dosing intervals (EDIs) with lanreotide autogel 120 mg are effective and wellreceived among patients with acromegaly who have achieved biochemical control with monthly injections of long-acting somatostatin analogues (SSAs). We further evaluated the effectiveness of lanreotide autogel 120 mg delivered at EDIs (>4 weeks) in routine clinical practice. Methods Cross-sectional, multicentre, observational study conducted to determine the effectiveness-measured by control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…The GoF indicators used for establishing the structural model demonstrated values of >0.75, demonstrating the substantial t of the model. Finally, the QoL in this population of patients with acromegaly was in line with the results of previous studies, showing that psychological status has a greater impact on QoL in this population (27).…”
Section: Discussionsupporting
confidence: 91%
“…The GoF indicators used for establishing the structural model demonstrated values of >0.75, demonstrating the substantial t of the model. Finally, the QoL in this population of patients with acromegaly was in line with the results of previous studies, showing that psychological status has a greater impact on QoL in this population (27).…”
Section: Discussionsupporting
confidence: 91%
“…The GoF indicators used for establishing the structural model demonstrated values of > 0.75, demonstrating the substantial fit of the model. Finally, the quality of life in this population of patients with acromegaly was in line with the results of previous studies, showing that psychological status has a greater impact on quality of life in this population [ 28 ]. Some study examined the quality of life and the associated factors in patients with acromegaly indicated quality of life is reduced in treated patients with acromegaly.…”
Section: Discussionsupporting
confidence: 91%
“…Though not frequently reported, median time since diagnosis of acromegaly varied from 1.4 (interquartile range 0.9–3.5 years) to approximately 14 years (range 1.5–27.1 years) across studies in which patients were not newly diagnosed. The majority of studies reported that patients had previously received pharmacological treatment for acromegaly at standard or unreported intervals: SRLs (n = 22 [ 36 , 38 51 , 55 61 ]), pegvisomant monotherapy (n = 4 [ 36 , 38 , 48 , 51 ]), and pegvisomant combination therapy (n = 2 [ 37 , 51 ]). Median duration of previous treatment was not systematically reported, but studies often required that patients were receiving their previous treatment for ≥ 6 months to be eligible for study entry.…”
Section: Resultsmentioning
confidence: 99%
“…Control of IGF-I levels was reported at study end with LAN administered at EDIs in ≥ 70% of patients in all four studies in which some, all or an unreported proportion of patients had controlled IGF-I at baseline [ 49 , 51 , 55 , 57 ]. Additionally, control of IGF-I levels was achieved with LAN at EDIs by study end in 33%–65% of patients in studies where no patients had controlled IGF-I levels at baseline (n = 2/2 studies [ 52 , 53 ]).…”
Section: Resultsmentioning
confidence: 99%